Three new diterpenoids from Aralia dumetorum. Issue 4 (3rd April 2019) - Li, Yan-Hong; Li, Hong-Rui; Yang, Chun-Tao; Tian, Kai; Yang, Cui; Sun, Jing-Xian; Wang, Wei; Huang, Xiang-Zhong
Abstract: Three new diterpenoids, dumetoranes A (1 ) and B (2 ), melanocane B (3 ), together with four known ones including melanocane A (4 ), ent -15 S, 16-dihydroxypimar-8(14)-en-19-oic acid (5 ), ent -pimara-8(14), 15-diene-19-oic acid (6 ), and ent -pimara-8(14), 15-diene-19-ol (7 ) were obtained from the ethanol extract of the roots of Aralia dumetorum . Their structure elucidation was achieved by the methods of spectroscopic HRMS, IR, NMR, and by comparison with literature. The cytotoxicities of compounds1 –3 and5 were assayed by in vitro MTT methods. Abstract :